(untitled) (Linguostylistic Studies, 2016)
The article is devoted to the analysis of peculiar features of the lexicon concerning various designations of smell in the M. Khvyliovyi’s small prose. A number of the literary and figurative odourative nominations have been revealed. In the focus of attention is the semantic classification of odouratives, their grammatical expression and stylistic importance in the context of works of art. The author states that in the works by M. Khvyliovyi the names of smell are mostly transferred by nouns and verbs. All the odouratives are divided into several semantic groups: smells of nature (flowers, herbs, fruits), smells of people, dwellings, food, beverages, abstract notions, etc.. Odourative nominations create interesting, deep, concrete sensory images in the aesthetic system of the writer’s artistic language. A number of the authors’ individual names of smell are analyzed. It has been concluded that besides the function of the direct naming of a smell, the odouratives in the works by M. Khvyliovyi perform also evaluative and emotionally expressive role. Key words: odour, odour/smell name, odourative lexicon, odouratives, nomination, smell nomination. References